ANALISIS PERSONAL BRANDING GIBRAN RAKABUMING RAKA DALAM PEMBENTUKAN POLITICAL IMAGE DI MEDIA SOSIAL X - Fadhilah, Saskia Nurul; Vanel, Zon (Jurnal Studi Ilmu Politik, 2024)
Political image can be formed through the use of various media. Social media that now become a trend can be utilized by political actor to support success of ongoing activities or simply just to increase popularity. While forming political image, a political actor can present their personal branding through social media. Using qualitative descriptive methods and theory by Peter Montoya, author applying 8 laws of the formation of personal branding such as: specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill to analyze how Gibran’s personal branding forms his political image. Gibran fulfilled all the laws of forming personal branding dan show improvement result of his political image based on additional data from author’s independent survey.